2023
DOI: 10.3920/bm2022.0091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lactobacillus crispatus-containing oral and vaginal probiotics on vaginal health: a randomised double-blind placebo controlled clinical trial

Abstract: Health of reproductive tract is tightly associated with balance of microbial communities in this area. Bacterial vaginosis (BV) and vulvovaginal candidiasis (VVC) represent common disturbances of vaginal communities. Vaginal discharge due to BV or VVC is a very frequent reason for visiting gynaecologist. We aimed to evaluate the impact of the novel evidence-based probiotics on BV and VVC patients. The study group included 89 BV and 93 VVC patients (aged 18-50 years) who were recruited into randomised double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Therefore, ethnicity might be a key factor. Aside from these two well-known Lactobacillus strains, other strains such as L. acidophilus GLA-14, L. crispatus LMG S-29995, L. crispatus DSM32717, L. crispatus DSM32720, L. paracasei LPC-S01, and L. rhamnosus HN001 have also been used orally in clinical investigations ( Russo et al., 2019a ; Koirala et al., 2020 ; Reznichenko et al., 2020 ; Mändar et al., 2023 ). These trials revealed that oral probiotics can enhance the recovery rate and relieve the symptoms of BV, as well as improve the vaginal microbial profile.…”
Section: Probiotic Lactobacilli In the Treatment Of Vaginal Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, ethnicity might be a key factor. Aside from these two well-known Lactobacillus strains, other strains such as L. acidophilus GLA-14, L. crispatus LMG S-29995, L. crispatus DSM32717, L. crispatus DSM32720, L. paracasei LPC-S01, and L. rhamnosus HN001 have also been used orally in clinical investigations ( Russo et al., 2019a ; Koirala et al., 2020 ; Reznichenko et al., 2020 ; Mändar et al., 2023 ). These trials revealed that oral probiotics can enhance the recovery rate and relieve the symptoms of BV, as well as improve the vaginal microbial profile.…”
Section: Probiotic Lactobacilli In the Treatment Of Vaginal Infectionsmentioning
confidence: 99%
“…These trials revealed that oral probiotics can enhance the recovery rate and relieve the symptoms of BV, as well as improve the vaginal microbial profile. As shown in Figure 2 , in addition to oral delivery, intravaginal administration is becoming increasingly popular among clinical studies ( Marcotte et al., 2019 ; Baldacci et al., 2020 ; Cohen et al., 2020 ; Armstrong et al., 2022 ; Mändar et al., 2023 ), possibly because intravaginal administration avoids the passage of lactobacilli into the highly acidic stomach, preventing loss of probiotics and accelerating the onset of effect. Compared to orally administered probiotics, which reach the vagina in approximately seven days, Lactobacillus strains administered intravaginally show effects in two to three days ( Mogha and Prajapati, 2016 ).…”
Section: Probiotic Lactobacilli In the Treatment Of Vaginal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which probiotics exert beneficial health effects can be summarized in three categories (Hill et al., 2014): Broad range of mechanisms commonly studied in probiotics. Examples: colonization resistance and competitive exclusion of pathogens (Mändar et al., 2023; Saracino et al., 2020; Stavropoulou & Bezirtzoglou, 2020), production of acids and short‐chain fatty acids (SCFAs) (Lim et al., 2023; Wang et al., 2023), regulation of intestinal transit and normalization of disturbed microbiota (Dahiya & Nigam, 2023b), and increased intestinal cell renewal (Gou et al., 2022; Hou et al., 2021; Tong et al., 2023). Mechanisms frequently observed in most probiotic strains.…”
Section: Addition Of Dietary Supplements—diversification Of Functions...mentioning
confidence: 99%
“…Rare mechanisms present in only a few strains of a given species. Examples: those responsible for neurological (Dahiya & Nigam, 2023a), detoxification (Kariyawasam et al., 2021; Mahjoory et al., 2023), immunological and endocrine effects (Mändar et al., 2023), and the production of specific bioactive substances (Sun et al., 2023). …”
Section: Addition Of Dietary Supplements—diversification Of Functions...mentioning
confidence: 99%